SAT0266 Safety Assessment of Biological Agents Used in Pediatric Rheumatic Diseases, Single Center Results. (15th July 2016) - Sozeri, B.; Gunduz, Z.; Dusunsel, R.; Pac Kisarslan, A.; Dursun, I.; Poyrazoglu, H.
Abstract : Background: In recent years, the biologic drugs has led to a dramatic change in the management of rheumatic diseases in children. Currently available biologics include TNF-α blockers, agents that target IL-1 and IL-6, T-cell costimulation inhibitors and antibodies against the CD20 molecule present on B cells. The studies about the long term safety of biologic agents (BA) in pediatric patients with rheumatic diseases are still limited. Objectives: The aim of this study was carry out a safety evaluation of biologic agents in patients with rheumatic disease Methods: This was retrospective study in Erciyes University Faculty Medicine, the tertiary center for pediatric rheumatology in Turkey. We recruited the patients who were diagnosed a rheumatic disease and treated with a biologic agent (BA) between 2009 and 2015. Adverse events (AEs) were categorized and graded based on the Common Terminology criteria for AEs (CTCAE). Grades 3–5 were considered SAEs. The time until discontinuation of BA was counted as patient-years (PY). Results: We included 127 consecutive patients: Juvenile idiopathic arthritis (n=102, 80.3%), Familial Mediterranean fever (n=9, 7.8%), Uveitis (n=7, 5.5%), sarcoidosis (n=3, 2.4%), Systemic lupus erythematosus (n=2, 1.6%), Hyperimmunglobulin D syndrome (HIDS) (n=2, 1.6%), Takayasu arteritis (n=1, 0.8%), Tumor necrosis factor receptor associated periodic syndrome (TRAPS) (n=1, 0.8%). The median age of the patients at diagnosis was 91 months [interquartile range (IQR) 60–138), while the median age at the time of treatment with biologic therapy was 144 (IQR 90–184) months. The median disease duration prior to treatment with biologics was 22 months (IQR 8–49). A total of 241.3 patient years (PY) were included: 132 py (72 patients) for etanercept, 44.5 (41) for adalimumab, 23 (20) for tocilizumab, 22 (13) for canakinumab, 7.7 (9) for infliximab, 4.2 (15) for anakinra, 6 (7) for abatacept and 1.9 (2) for rituximab. A total of 113 patients (89%) were on methotrexate prior to biologics and 90 (71%) during biologics. A total of 38 patients (30%) had been on two or more biologics, 7 (5.5%) on three, 5 on four (3.9%) and 1 on five. A total of 35 patients (27.6%) had at least one AE. Those with AEs 45 months (IQR 57) had a significantly longer median follow-up of 31 months (IQR 41) than those without an AE (p=0.01). Forty-five patients experienced 93 AEs (38.5/100 py). Of those AEs, 20 were reported as serious AEs (8.3 /100 py). The SAEs were lower with anti TNF alpha agents than others (6.8 for ETN, 21.7 for TOS, 4.5 for ADA, 25.9 for INF, 4.5 for CAN, 23.8 for ANK, 33.3 for ABT) (p=0.00). Eight of the SAEs (40%) were classified as noninfectious (infusion reaction, anaphylaxis, vasculitis, macrophage activation syndrome, seizure and glomerulonephritis) were documented. Three patients on ETN developed reactivation of latent tuberculosis. No deaths, malignancies, opportunistic infections, demyelinating diseases, or lupus-like reactions were observed during biologic agents exposure. Conclusions: Here in, we presented safety data comparing biologic drugs in pediatric patients retrospectively. The frequency of mild infections and latent tuberculosis was higher on Anti TNF alpha drugs, but sAEs were lower than others. To better define the safety profile of biologic drugs need for prospective studies and large cohorts. Disclosure of Interest: None declared